STRATEGI PEMBERDAYAAN EKONOMI MASYARAKAT DI SEKITAR KAWASAN HUTAN LINDUNG REG. 20 KABUPATEN PESAWARAN, LAMPUNG - Fitriani Fitriani; Cholid Fatih; Teguh Budi Trisnanto; Zainal Mutaqin (Politeknik Negeri Lampung., 2021)
The main problems faced in managing the Pesawaran forest area are the activities of forest encroachment, illegal logging and mining, and also shifting of boundaries that threaten the function of the forest. This research aims to ensure the design of strategies for community economic empowerment in forest areas so that they can be responsible for forest rehabilitation activities. Gayau Village, Padang Cermin sub-District, Pesawaran Region, Lampung represented as the research location that bordered with the Protection Forest 20 Region. Respondents were determined by purposive sampling method amount of 40 people. It was the representation of community leaders, village officials, farmer institutions (poktan/Gapoktan), and farmers who carry out agricultural activities around forest areas. The data collection method using a Rapid Rural Appraisal (RRA) and Focus Group Discussion (FGD) approach. The data analysis method was descriptive qualitative method using SWOT analysis. Based on the analysis results show that strategy should consider the strengthen the community forest management based on Good Agriculture Practices (GAP) farming. This is in quadrant I potition or in growth conditions. It means that the appropriate strategy is cpmbining the Strength and Opportunity condition. Then the appropriate strategy is a concentration through horizontal integration of farm diversification. The production of intercropping plants with high economic value is an important alternative. Increasing farm productivity needs through by improving the quality of cultivation with GAP principles. This strategy is included in the growth strategy by expanding community activities and developing information and communication networks in regions that have the same program. Exploration of alternative income growth from non-timber resources requires assistance from capital institutions, the extension institution (state or private) and access to technology.